(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
High salinity environments – including hypersaline lakes, coastal salt marshes, mangrove forests, sabkhas, and solar evaporation ponds – impose severe osmotic and ionic stress on resident biota, selecting for a remarkable diversity of molecular, physiological, and behavioural adaptations that collectively define halotolerant and halophilic life history strategies. This study conducted a comparative analysis of salinity adaptation mechanisms across 84 animal species spanning six taxonomic classes (Crustacea, Insecta, Pisces, Reptilia, Aves, and Mammalia) inhabiting salinity gradients from 5 to 340 g/L in 16 hypersaline systems across five continents. Osmoregulatory performance – quantified as the ability to maintain haemolymph or plasma osmolality within 10% of isosmotic conditions across the full habitat salinity range – was achieved by 71.4% of studied species and was significantly predicted by gill surface area index (PGLS: R2 = 0.74, p < 0.001), renal corpuscle density (R2 = 0.68, p < 0.001), and expression levels of Na+/K+-ATPase in osmoregulatory epithelia (R2 = 0.81, p < 0.001). Ion exclusion efficiency in avian salt gland secretors averaged 94.7% +- 3.2% for Na+ across flamingo, gull, and pelican species, closely matching theoretical thermodynamic maxima. Behavioural thermoregulatory responses – including microhabitat selection for lower-salinity freshwater seeps and temporal activity shifting to cooler periods minimising evaporative concentration – were quantified via GPS telemetry in four focal mammalian and avian species. Molecular adaptation signatures identified by transcriptomic analysis included significant upregulation of heat shock proteins, compatible solute synthesis genes, and aquaporin water channels in halotolerant relative to freshwater conspecifics (fold change: 2.8-6.4x; all FDR < 0.05). These findings provide an integrated mechanistic framework for understanding biodiversity persistence in hypersaline ecosystems under intensifying climate-driven salinisation.